Language-based user management in interactive networked collaborative environment / Assoc. Prof. Siti Zaleha Zainal Abidin, Dr. Nasiroh Omar and Zainura Idrus - Zainal Abidin, Siti Zaleha; Omar, Nasiroh; Idrus, Zainura (Research Management Institute (RMI), 2012)
In interactive networked collaborative virtual environment (NCVE), users work in a group to involve in activities such as game, business transaction and learning. However, their existence is not visibly presence. Therefore, there is a crucial need to represent the invisible users so that users know with whom they are interacting with (presence), when to communicate (state) and what to do (role) during the collaboration. Unlike any group work or organizations, users in virtual space are dynamic. They can change their role and states frequently such as joining or leaving the group work at any time. They can engage in the collaboration only for a period of time or until the goals are achieved. This research will investigate and propose the generic way of managing invisible users (their presence, states and roles) through language-based approach. The novelty lies on the new design of language constructs for managing dynamic users. The language constructs offer faster and easier development of collaborative applications (game, commerce, defense, banking, education).